Behavioural and electrophysiological responses of the phlebotomine sandfly Lutzomyia longipalpis (Diptera: Psychodidae) when exposed to canid host odour kairomones - Dougherty, M. J.; Guerin, Patrick; Ward, R.D.; Hamiltion, J.G.C. (Wiley, 1999)
Compounds from the odour-producing glands of the fox Vulpes vulpes were collected. This complex mixture of compounds was used to stimulate the 'ascoid' olfactory organs of female sandflies in single sensillum and gas chromatography-linked single sensillum recordings. Sixteen of these compounds were identified using gas chromatography-linked mass spectrometry and amounts present were determined. The compounds fell into four organic classes: ketones, carboxylic acids, alcohols and aldehydes. Specific neurones present in the ascoid sensillum that responded to each of these classes of compound were characterized.
A bioassay chamber was developed that gave female sandflies the choice of two odour sources. Female sandflies were attracted upwind by fox odour and were trapped in closer proximity to the fox odour port than the control port. Synthetic compounds were recombined in appropriate quantities to mimic the fox odour. In this bioassay, the synthetic blend attracted sandflies upwind, and again they were caught closer to the test port than the control port. Furthermore, the synthetic fox odour induced an electrophysiological response from neurones in the ascoid sensillum that was very similar to that induced by natural fox odour. No synthetic compound alone induced the same behavioural response from sandflies as did whole fox odour. However, benzaldehyde, 4-hydroxy-4-methyl-2-pentanone and 4-methyl-2-pentanone alone did cause sandflies to fly upwind and to be caught closer to the test port than the control.
Keywords: attractant; behaviour; electrophysiology; fox odour; Lutzomyia longipalpis; kairomones; odour bioassay; sandfly; sensillum